2020
DOI: 10.1159/000508512
|View full text |Cite
|
Sign up to set email alerts
|

Urology in the Time of Coronavirus: Reduced Access to Urgent and Emergent Urological Care during the Coronavirus Disease 2019 Outbreak in Italy

Abstract: The coronavirus disease 2019 (COVID-19) pandemic has put a substantial burden on the Italian healthcare system, resulting in the restructuring of hospitals to care for CO-VID-19 patients. However, this has likely impacted access to care for patients experiencing other conditions. We aimed to quantify the impact of COVID-19 on access to care for patients with urgent/emergent urological conditions throughout Italy. Materials and Methods: A questionnaire was sent to 33 urological units in the AGILE consortium, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
32
0
4

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 8 publications
5
32
0
4
Order By: Relevance
“…Arch Med Sci or ureteral stenting), transurethral resection of bladder tumor, and testicular detorsion between a pre-COVID period in 2020 and during the massive outbreak in Italy [6]. In our cohort, the distribution of the interventions was non-significantly different with an 8% decrease in absolute numbers of endoscopic procedures in 2020.…”
mentioning
confidence: 55%
See 1 more Smart Citation
“…Arch Med Sci or ureteral stenting), transurethral resection of bladder tumor, and testicular detorsion between a pre-COVID period in 2020 and during the massive outbreak in Italy [6]. In our cohort, the distribution of the interventions was non-significantly different with an 8% decrease in absolute numbers of endoscopic procedures in 2020.…”
mentioning
confidence: 55%
“…In China, Italy, the UK, and the US, initial reports suggest a decrease in visits to emergency departments (EDs) and admissions for urgent cardiac and neurological conditions [1][2][3][4][5]. In Italy and Portugal, there is also evidence of a decrease in ED visits and admissions for urgent urologic conditions but mostly reported in studies of a single center or a short duration [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Several cross-sectional surveys, investigating the impact of COVID-19 on urological services worldwide, confirmed that the pandemic has imposed great challenges to urology health care providers. In fact, a significant cut-down in urology clinics, outpatient procedures, major surgeries, and urgent/emergent urological care has been reported 2 , 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Due to the density of patients in the wards participating in this study in our pandemic hospital and the possibility of transmission to health studies, the study was limited to the I-PSS survey only. The patients were divided into three groups based on their scores in the I-PSS survey: group 1: mild (0-7), group 2: moderate (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19), and group 3: severe (20-35). The patients' findings at presentation such as fever, cough, sore throat, headache, fatigue, muscle pain and dyspnea, and the current accompanying diseases (diabetes mellitus, hypertension, chronic lung diseases, malignancy, chronic organ failure, etc.)…”
Section: Methodsmentioning
confidence: 99%